Avoiding common errors in the emergency department - Mattu, Amal; Chanmugam, Arjun S.; Swadron, Stuart P.; Woolridge, Dale; Winters, Michael E. (Wolters Kluwer, 2017)
"In a conversational, easy-to-read style, Avoiding Common Errors in the Emergency Department, 2nd Edition, discusses 365 errors commonly made in the practice of emergency medicine and gives practical, easy-to-remember tips for avoiding these pitfalls. Chapters are brief, approachable, and evidence-based, suitable for reading immediately before the start of a rotation, used for quick reference on call, or read daily over the course of one year for personal assessment and review. Key Features: Coverage includes psychiatry, pediatrics, poisonings, cardiology, obstetrics and gynecology, trauma, general surgery, orthopedics, infectious diseases, gastroenterology, renal, anesthesia and airway management, urology, ENT, and oral and maxillofacial surgery. Completely revised and rewritten by many new authors, as well as returning authors who bring a fresh perspective to new subjects. New key points at the end of each chapter present must-know information in an easy-access, bulleted format. Ideal for emergency medicine physicians, residents, and attendings; emergency nurse practitioners, PAs who practice in the ED, and primary care physicians in urgent care centers. Your book purchase includes a complimentary download of the enhanced eBook for iOS, Android, PC & Mac. Take advantage of these practical features that will improve your eBook experience: the ability to download the eBook on multiple devices at one time -- providing a seamless reading experience online or offline. Powerful search tools and smart navigation cross-links allow you to search within this book, or across your entire library of VitalSource eBooks Multiple viewing options offer the ability to scale images and text to any size without losing page clarity as well as responsive design. The ability to highlight text and add notes with one click"--Provided by publisher.